Impact of early Danian environmental perturbations on mid-latitude planktic foraminiferal assemblages from the ODP Site 1262 (South Atlantic Ocean) ... - Krahl, Guilherme; Arenillas, Ignacio; Gilabert, Vicente; Kochhann, Karlos G. D.; Bom, Marlone H. H.; Fauth, Gerson; Arz, José Antonio (Zenodo, 2023)
After the mass extinction at the Cretaceous/Paleogene (K/Pg) boundary (~66 Ma), life forms quickly radiated to occupy ecological niches in the world’s oceans. Nevertheless, the aftermath of the Chicxulub impact, the massive volcanism of the Deccan Traps and climatic perturbations endured during the early Danian. The impact of consequent carbon cycle perturbations on nascent plankton communities, such as the Dan-C2 event (~65.80 to ~65.71 Ma), is still poorly known. In this work, we present a detailed study of planktic foraminiferal assemblages from Ocean Drilling Program (ODP) Site 1262 (Walvis Ridge, South Atlantic Ocean), spanning the first ~400 kyr of the Danian. No relevant perturbations in planktic foraminiferal assemblages and carbonate preservation indices have been identified at Site 1262 during the Dan-C2 event. Approximately 50 kyr before the beginning of the Dan-C2 event, a Hg-rich interval, potentially linked to the emplacement of the Ambenali Formation of the Deccan Traps massive volcanism, is ... : This work was supported by grant PID2022-136233NB-I00 funded by MCIN/ AEI /10.13039/501100011033/and by ERDF A way to make Europe. Vicente Gilabert acknowledges support from Ministerio de Universidades (MIU) and European Union (Margarita Salas post-doctoral grant) funded by European Union-NextGeneration EU. ...